Detecting Financial Statement Fraud in Indonesian Companies: The Beneish M-Score Model - Ghazi Althof Ayyasy; Isnawati (SIMAK, 2026)
This study aims to detect financial statement fraud in Indonesian companies using the Beneish M-Score model. The research covers 622 companies from ten sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024, with a total of 2,488 financial statements. The data was obtained from the IDX's published financial reports and analysed using eight Beneish M-Score ratios to classify companies into manipulator and non-manipulator categories. The results show that 34.03% of companies were identified as manipulators, while the remaining 65.97% were classified as non-manipulators. The technology sector had the highest percentage of manipulators (45%), followed by the raw materials sector (37%) and energy (36.49%). Conversely, the transportation (24.04%) and health (27.68%) sectors had the lowest percentages. These findings confirm that financial statement fraud remains a serious problem, with varying levels of risk across sectors. The implications of the study emphasise the importance of strengthening corporate governance, the role of external audits, and regulatory oversight to prevent manipulative practices. In addition, this study contributes to academic literature by providing a comprehensive overview of cross-sector manipulation trends in Indonesia.